Work-Life Balance : A Review and Future Research Agenda - Rashmi, Kumari; Kataria, Aakanksha; Singh, Reeta (Prabandhan: Indian Journal of Management, 2021)
This article aimed to provide an integrated review of the research in the area of work-life balance (WLB) that has attracted the attention of researchers in recent years. It has been due to contemporary demographic, technological, environmental changes and also due to heightened concern among individuals for greater balance in work and personal life domains. WLB is a holistic concept that focuses on integrating the work and personal life activities of the individuals. This study contributed to the area of the work-life interface by scrutinizing the conceptualization of the key constructs, their meaning, and the influence of various antecedents and their consequences. Besides, this article also highlighted significant gaps and recommended avenues for future research. While reviewing this topic, it was observed that most prominently, researchers have put more emphasis on work-family conflict (WFC), while the WLB concept has received less attention in work-life research. Determinants of the work-life interface such as organizational domain predictors, dispositional (individual) predictors, life domain predictors, and demographic predictors are the prominent research areas in this field. The outcomes of the work-life interface identified in this field included work domain predictors and non-work domain predictors. The majority of the research studies in this field have taken place in developed economies in contrast to developing economies. Empirical research with regression-based models for analysis is the most popular research design.